DEVELOPMENT OF A SELF-CARE (WELL-BEING) GUIDANCE E-MODULE TO ADDRESS ACADEMIC STRESS AMONG BROKEN-HOME STUDENTS AT SMAN 1 MAJENE - Arianto, Nur Afifah; Harum, Akhmad; Amirullah, M (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
The purpose of this study is to develop an e-module for self-care counseling services to address stress caused by broken homes among students at SMAN 1 Majene. The research method uses the Research and Development (R&D) model with the ADDIE approach, which includes the analysis, design, development, implementation, and evaluation stages. Data dikumpulkan melalui wawancara, angket, validasi ahli, dan tes kepraktisan guru BK. The results of the study show that: (1) the needs analysis identified that students from broken homes experience learning stress, which is characterized by anxiety, a lack of motivation, and difficulty concentrating; (2) the developed e-module consists of four main topics: academic stress, self-care, social support, and mindfulness; (3) the results of the expert validation of the materials and media show the category "very valid"; and (4) the practicality test for guidance counselors shows the category "very practical." Therefore, this e-module is suitable for use as a supporting medium for counseling services to address stress in students.